A rapid and sensitive fluorescence method for detecting urine formaldehyde in patients with Alzheimer's disease. (March 2019) - Ai, Li; Wang, Jun; Li, Tingting; Zhao, Chang; Tang, Yonghe; Wang, Weishan; Zhao, Shengjie; Jiang, Wenjing; Di, Yalan; Fei, Xuechao; Luo, Hongjun; Li, Hui; et al.
Background: Morning urine formaldehyde concentrations could predict the severe degree of dementia in patients with post-stroke dementia and Alzheimer's disease. However, the routinely available technique of high-performance liquid chromatography (HPLC) for detecting urine formaldehyde requires expensive and sophisticated equipment. Methods: We established a fluorescence spectrophotometric method by using a formaldehyde-specific fluorescent probe-NaFA (λex/em = 430/543 nm). As a standard reference method, the same batch of urine samples was analysed by HPLC with a fluorescence detector (λex/em = 346/422 nm). Then we compared the limits of detection and the limits of quantization detected by these two methods and addressed the relationship between urine formaldehyde and human cognitive ability. The Mini-Mental State Examination (MMSE), Clinical Dementia Rating and Activities of Daily Living scale were used to evaluate cognition function in 30 Alzheimer's disease patients and 52 healthy age-matched controls. Results: Limits of detection and limits of quantization (1.27 and 2.48 μ M) of the NaFA probe method were more accurate than Fluo-HPLC (1.52 and 2.91 μ M). There was no difference in the detected formaldehyde values within day and day-to-day. Notably, only 3/82 urine formaldehyde concentrations detected by NaFA probe were below zero, while 12/82 of the values analysed by Fluo-HPLC were abnormal. More importantly, there were negatively correlated between urine formaldehyde concentrations detected by NaFA probe and MMSE scores, but positively correlated with Clinical Dementia Rating scores in Alzheimer's disease patients. Conclusions: This detecting urine formaldehyde method by NaFA probe was more rapid, sensitive and accurate than Fluo-HPLC.